Clinical and Genetic Analysis of Costa Rican Patients With Parkinson's Disease - Torrealba-Acosta, Gabriel; Yu, Eric; Lobo-Prada, Tanya; Ruíz-Martínez, Javier; Gorostidi-Pagola, Ana; Gan-Or, Ziv; Carazo-Céspedes, Kenneth; Trempe, Jean-François; Mata, Ignacio F.; Fornaguera-Trías, Jaime (Frontiers in Neurology, 2021)
Background: Most of research in genomics of Parkinson’s disease (PD) has been done in subjects of European ancestry leading to sampling bias and leaving Latin American populations underrepresented. We sought to clinically characterize PD patients of Costa Rican origin and sequence familial PD and atypical parkinsonism-associated genes in cases and controls. Methods: We enrolled 118 PD patients with 97 unrelated controls. Collected information included demographics, exposure to risk and protective factors, motor and cognitive assessments. We sequenced coding and untranslated regions in familial PD and atypical parkinsonism-associated genes including GBA, SNCA, VPS35, LRRK2, GCH1, PRKN, PINK1, DJ-1, VPS13C, ATP13A2. Results: Mean age of PD probands was 62.12 ± 13.51 years, 57.6% were male. The frequency of risk and protective factors averaged ~45%. Physical activity significantly correlated with better motor performance despite years of disease. Increased years of education were significantly associated with better cognitive function; whereas hallucinations, falls, mood disorders and coffee consumption correlated with worse cognitive performance. We did not identify an association between tested genes and PD or any damaging homozygous or compound heterozygous variants. Rare variants in LRRK2 were nominally associated with PD, six were located between amino acids p.1620-1623 in the C-terminal-of-ROC (COR) domain of Lrrk2. Nonsynonymous GBA variants (p.T369M, p.N370S, p.L444P) were identified in three healthy individuals. One PD patient carried a pathogenic GCH1 variant, p.K224R. Discussion: This is the first study that describes sociodemographic, risk factors, clinical presentation and genetics of Costa Rican patients with PD; adding information to genomics research in Latino population.